A location-based services and Google maps-based information master system for tour guiding. (August 2016) - Yang, Sheng-Yuan; Hsu, Chun-Liang
Highlights: A location-based services and Google maps-based Dr.What-Info multi-agent system is proposed. An archeologic site in New Taipei City, Taiwan, for testing purposes, produces results regarding the completeness and feasibility of the proposed architecture. The deep and complete system developments, displays, and corresponding experiments and comparisons show that the research results demonstrate performance superiority over a number of previous studies. Abstract: This paper aims to develop a location-based services supported Dr.What-Info system, i.e. a master multi-agent system on what the information is, using Google maps and an image recognition technology as a tourism information provider and as a route planner for tourists. Users can have great fun during vacation travels through an easy-to-use interface, integrating smartphone GPS function, a QR/Bar code reader and easy access to a cloud database, to find all of the required web services. In particular, given an archeological site in New Taipei City, Taiwan, for testing purposes, the presented system is demonstrated not only as a provider of information on popular tourist attractions, but also as a high performance GPS navigation device to guide users toward their desired destinations. The complete system developments, displays, and corresponding experiments and comparisons show that the research results demonstrate performance superiority over a number of previous studies. Graphical abstract: